PENGARUH MEDIA PEMBELAJARAN FLASHCARD TERHADAP KEMAMPUAN MENGHITUNG PADA MATA PELAJARAN MATEMATIKA SISWA KELAS I UPT SPF SD INPRES BONTOMANAI - Nur Halidah; Baharullah; Andi Ardhillah Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine how much the ability to calculate mathematics through flashcard learning media and to determine the effect of flashcard learning media on the ability to calculate in mathematics subjects. This type of research is Pre-experimental research. With the research design is One Group Pretest-Posttest Design. The population of this study was all students of grade I UPT SPF SD Inpres Bontomanai, which consists of two classes namely class IA and IB. While the sample used in this study was simple cluster sampling. Simple cluster sampling is a random sampling technique from various clusters in a population. The sample taken in this study was class IA as many as 28 students. The research instrument used was a pretest and posttest test sheet. The data analysis technique used was descriptive statistical data analysis and inferential data analysis. The results of the study showed that the average score of the initial ability test before the application of flashcard learning media (pretest) was 39.28 with a standard deviation of 17.089. From these results, 2 (7.12%) students completed the test and 26 (92.85%) students did not complete it, while the average score after the application of flashcard learning media (posttest) was 84.10 with a standard deviation of 10.71. From these results, 3 (10.71%) students did not complete the test and 25 (89.28%) students completed the test, this means that classical completeness was achieved. This shows that flashcard learning media has a positive effect on improving students' counting abilities. The results of the Paired Sample T-Test test show that the significance value (2-tailed) is <0.000. This significance value is much smaller than the significance level of 0.05, so H0 is rejected and H1 is accepted. Thus, H0 is rejected and H1 is accepted, indicating that there is a significant difference in students' calculation ability before and after treatment. It can be concluded that the application of flashcard learning media has an effect on improving students' calculation ability.